Strategi Pengembangan Sumber Daya Perpustakaan Pusat Universitas Pendidikan Indonesia Melalui Kerja Sama Perpustakaan IAIN Salatiga - Helmi Rabani, Rafi; Prijana, Prijana (Jurnal Pustaka Ilmiah, 2023)
Problems in libraries can be overcome one way by collaborating between libraries. Collaboration can be carried out by any type of library, including state university libraries. College libraries have the same functions as libraries in general and the functions included in the Tri Dharma of Higher Education include education, research and community service. The development of library resources at the Central Library of the Indonesian Education University is carried out in collaboration with the Salatiga State Islamic Institute Library. This research aims to find out what cooperation looks like, how cooperation is carried out, and what are the challenges in carrying out collaboration between the two libraries. The research method used is a qualitative research method and data collection techniques in the form of interviews with the Head of the Library Services Division of the UPI Central Library. The research results show that the cooperation carried out is cooperation in the field of information services and is bound by a memorandum of agreement with six scopes of cooperation. Several challenges were found, namely in terms of busyness of library managers, permission from the head of the library, and budget in carrying out collaboration. There are several scopes that cannot be realized in the implementation of cooperation. This cannot be used as a barrier to working together, but is a motivation for both parties because the priority is service to users.